ANALISIS KEMAMPUAN MEMECAHKAN MASALAH MATEMATIKA SEKOLAH MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA UNIVERSITAS KATOLIK WIDYA MANDALA MADIUN - Yohanes, Rudi Santoso (Universitas Negeri Surabaya, 2019)
This study aims to understand the profile of school mathematic problem solving skills of the students of Mathematic Education Program (PSP Matematika) in Widya Mandala Madiun Catholic University (UKWMM). This study is a descriptive-explorative qualitative research which involves 29 Mathematic Education Program students of UKWMM in the academic year of 2017-2018. The data are collected using Problem Solving Test of School Mathematics in the form of a subjective test which consists of 5 questions. The test is used to describe the profile of school mathematic problem solving skills of Mathematic Education Program students in UKWMM. The process of the students answering the problem solving test of school mathematics is also analyzed to describe the students weaknesses on solving the school mathematic problems. The result shows the students of Mathematic Education Program of UKWMM do not have good enough school mathematics problem solving skills. The analysis on the process while the students are answering the test also shows that most of the students are not accustomed to (or do not have enough experience on) solving problems that require higher order thinking skills. The students do not possess the strategy to solve the non-routine problems. The lack of curiosity and willingness of the students to solve the problem has become one of the factors that cause the lack of their mathematic problem solving skills.